The Use of Interactive Storytelling to Improve Reading Literacy Abilities in Islamic Cultural History at SMP IT Al Bina Masohi, Central Maluku Regency - Hapsah Mardjima; Anasufi Banawi; Muhajir Abd. Rahman (Yayasan Literasi Sains Indonesia, 2025)
One of the learning elements in Islamic Religious Education is the element of Islamic Cultural History (SKI). Through the right learning approach, Islamic Religious Education teachers play a role in improving literacy skills and reading comprehension of Islamic Cultural History events by using interactive storytelling methods. Interactive storytelling is not a contemporary learning method. However, interactive storytelling is rarely employed in the field of Islamic Religious Education studies, despite its potential to enhance the quality of learning, particularly in aspects such as literacy and storytelling skills. The purpose of this study is to describe and explain the planning, implementation, and implications of using interactive storytelling to improve the reading literacy skills of seventh-grade students in Islamic Cultural History material at SMP IT Al Bina Masohi. This type of research employs a qualitative approach, utilising data collection techniques that include observation, interviews, and documentation. The results of the study indicate that the use of interactive storytelling in the material of Islamic Cultural History at SMP IT Al Bina Masohi has been implemented quite effectively as an effort to improve reading literacy and foster storytelling skills.